Adsorption properties of radionuclides on BC3: the first principles study. (18th June 2022) - Zhou, Nan; Qin, Yong; Tan, Jie; Cheng, Jinjuan; He, Shuaixing; Li, Hai; Wu, Xijun
Abstract : The adsorption properties of BC3 nanosheets on radioactive metal atoms were systematically investigated based on the first principles approach of density functional theory (DFT). Following the adsorption of metal atoms by BC3, an electronic structure analysis was performed to determine the optimal adsorption sites and energies of metal atoms. The impact of temperature on the adsorption rate was calculated using the adsorption energy obtained from the first-nature principle. BC3 is more stable than graphene material, with less impact on adsorption rate at high temperatures, and forms chemical bonds with radionuclides, significantly enhancing adsorption performance (especially on Ag, transforming it from physical to chemisorption). The results indicate that the B-atom-doped graphene materials have a promising future for the post-treatment of radioactive effluents in nuclear wastewater. GRAPHICAL ABSTRACT: UF0001